Classification and regression trees, CART: a user manual for identifying indicators of vulnerability to famine and chronic food insecurity - Yohannes, Yisehac; Webb, Patrick (International Food Policy Research Institute, 1999)
This third book in the series, Classification and Regression Trees, CART ™ : A User Manual for Identifying Indicators of Vulnerability to Famine and Chronic Food Insecurity, by Yisehac Yohannes and Patrick Webb, is a manual outlining how to use CART software to conduct classification- and regression-tree analysis. The manual is based on IFPRI’s experiences from its famine research program, which was completed in 1998 with the publication of the book by Joachim von Braun, Tesfaye Teklu, and Patrick Webb, Famine in Africa: Causes, Responses, and Prevention. The manual shows how to use CART to identify in dicators of a number of outcomes, including food insecurity and vulnerability to famine. Examples are provided throughout using programs from CART.™